A current affair: electrotherapy in wound healing - Hunckler J; de Mel A (Journal of Multidisciplinary Healthcare, 2017)
Jerome Hunckler, Achala de Mel UCL Division of Surgery and Interventional Sciences, Faculty of Medical Sciences, University College London, London, UK Abstract: New developments in accelerating wound healing can have immense beneficial socioeconomic impact. The wound healing process is a highly orchestrated series of mechanisms where a multitude of cells and biological cascades are involved. The skin battery and current of injury mechanisms have become topics of interest for their influence in chronic wounds. Electrostimulation therapy of wounds has shown to be a promising treatment option with no-device-related adverse effects. This review presents an overview of the understanding and use of applied electrical current in various aspects of wound healing. Rapid clinical translation of the evolving understanding of biomolecular mechanisms underlying the effects of electrical simulation on wound healing would positively impact upon enhancing patient’s quality of life. Keywords: electrotherapy, wound healing, infection, bioelectric current, exogenous current, bioelectric medicine, electrical stimulation, chronic wound, acute wound